Element distribution in visual system, the optic chiasma, lateral geniculate body, and superior colliculus - Setsuko Tohno (2018)
To elucidate compositional changes of the visual system with aging, the authors investigated age-related changes of elements in the optic chiasma, lateral geniculate body, and superior colliculus, relationships among their elements, relationships among their brain regions from a viewpoint of elements, and gender differences in their elements by direct chemical analysis. After ordinary dissection at Nara Medical University was finished, the optic chiasmas, lateral geniculate bodies, and superior colliculi were resected from identical cerebra of the subjects. The subjects consisted of 14 men and 10 women, ranging in age from 75 to 96 years (average age=85.6±5.9 years). After ashing with nitric acid and perchloric acid, element contents were determined by inductively coupled plasma-atomic emission spectrometry. As the result, the average content of P was significantly higher in the optic chiasma and superior colliculus compared with the lateral geniculate body. Regarding age-related changes of elements, no significant changes with aging were found in seven elements of the optic chiasma, lateral geniculate body, and superior colliculus in the subjects more than 75 years of age. The findings that with regard to the relationships among elements, there were extremely significant direct correlations between Ca and Zn contents and significant inverse correlations betweenMg and Na contents were obtained in common in all of the optic chiasma, lateral geniculate body, and superior colliculus. It was examined whether there were significant correlations among the optic chiasma, lateral geniculate body, and superior colliculus in the seven elements and the following results were obtained: There were significant direct correlations between the optic chiasma and lateral geniculate body in both the P and Mg contents; there was a significant direct correlation between the optic chiasma and superior colliculus in the Fe content; and a significant direct correlation was found between the lateral geniculate body and superior colliculus in the Mg content. Regarding the gender differences in elements, it was found that both the Ca and Zn contents of the lateral geniculate body were significantly higher in women than in men. © Springer Science+Business Media, LLC 2010.